2001
DOI: 10.1097/00005176-200107000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Elastase 1 in Feces of Preterm and Term Infants

Abstract: The adult reference value for pancreatic E1 of greater than 200 microg/g feces can be applied to infants older than 2 weeks, independent of gestational age, birth weight, and the type of nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 12 publications
3
32
0
2
Order By: Relevance
“…However, after 1 year all infants exhibited normal fecal pancreatic elastase levels. Nissler et al 28 observed that fecal "elastase 1" was less than 200 µg/g in 17 of 148 infants (11.5%), and their median age was 37 weeks with a range of 1-313 days. The majority of infants exhibited normal levels (>200 µg/g) after 14 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, after 1 year all infants exhibited normal fecal pancreatic elastase levels. Nissler et al 28 observed that fecal "elastase 1" was less than 200 µg/g in 17 of 148 infants (11.5%), and their median age was 37 weeks with a range of 1-313 days. The majority of infants exhibited normal levels (>200 µg/g) after 14 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study of 148 infants without known bowel or pancreatic disorders showed that 96.8% of neonates had E1 levels above the 200 Ag/g cut-off by 2 weeks of age, independent of gestational age [31]. Pre-term babies had levels under 30 Ag/g up to 48 h after birth but 43% of term infants had normal adult values within 48 h of life.…”
Section: Determining Cut-off Valuesmentioning
confidence: 99%
“…Three children with BA had no result of serum amylase and lipase. Normal values are 1 200 g/g for FE1 [8][9][10][11] , ! 100 U/l for serum amylase, and !…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported to be a sensitive screening test for severe EPI [8][9][10] . In addition, the adult reference value for FE1 of greater than 200 g/g feces can be applied to infants older than 2 weeks [11] . The aim of the present study was to investigate the exocrine pancreatic function and common pancreatic function tests in children with different causes of cholestasis by measurements of FE1 and serum amylase and lipase levels.…”
Section: Introductionmentioning
confidence: 99%